2020
DOI: 10.1371/journal.pone.0237463
|View full text |Cite
|
Sign up to set email alerts
|

Bio-activating ultrafine grain titanium: RNA sequencing reveals enhanced mechano-activation of osteoconduction on nanostructured substrates

Abstract: Titanium is essentially absent from biological systems yet reliably integrates into bone. To achieve osseointegration, titanium must activate biological processes without entering cells, defining it as a bio-activating material. Nanostructuring bulk titanium reduces grain size, increases strength, and improves other quantifiable physical properties, including cytocompatibility. The biological processes activated by increasing grain boundary availability were detected with total RNA-sequencing in mouse pre-oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…7 Researchers have extensively explored the interaction of nanostructured alloys with physiological systems, which have been summarized in recent reviews. 2,[8][9][10] The results of these investigations demonstrate benefits including increased cell adhesion, proliferation, and differentiation for a wide range of cell types. Most recently, Reiss et al sequenced the RNA of bone-forming cells on nanostructured titanium to discover the mechanism by which the metal surface grain boundaries enhance osteoconduction.…”
Section: Medical Devicesmentioning
confidence: 91%
See 1 more Smart Citation
“…7 Researchers have extensively explored the interaction of nanostructured alloys with physiological systems, which have been summarized in recent reviews. 2,[8][9][10] The results of these investigations demonstrate benefits including increased cell adhesion, proliferation, and differentiation for a wide range of cell types. Most recently, Reiss et al sequenced the RNA of bone-forming cells on nanostructured titanium to discover the mechanism by which the metal surface grain boundaries enhance osteoconduction.…”
Section: Medical Devicesmentioning
confidence: 91%
“…Most recently, Reiss et al sequenced the RNA of bone-forming cells on nanostructured titanium to discover the mechanism by which the metal surface grain boundaries enhance osteoconduction. 10 The combination of enhanced biological properties with the superior mechanical properties of ultrafine grain alloys makes the pursuit of commercialization for trauma, orthopedic, and dental highly attractive.…”
Section: Medical Devicesmentioning
confidence: 99%
“…The resulting data files were downloaded and opened with JMP version 14 (SAS Institute, Cary, NC, USA) for data filtering and further analyses. Zipf’s power law is a graphic method employed to model complex phenomena ( Adamic, 2011 ) that has been used to identify low count theshold in environmental metagenomic shotgun sequence data ( Reiss, Guerra & Makhnin, 2016 ) and in a study of cell response to nanostructured titanium ( Reiss et al, 2020 ). Transcription profiles of tissue qualifies as a complex system and a low count cutoff was determined by a Ziph graph, in which the log abundance per gene, as measured counts per million (CPM) for all samples, is graphed against the log rank of each gene ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Network analysis can help detect the relationships between the biological processes and changes in gene expression relevant to the experiment. For example, using a workflow with two conditions, each with two replicates that consisted of pooled cells exposed to titanium of a specific grain size, gene expression differences revealed changes in biological processes associated with mechanotransduction ( Reiss et al, 2020 ). Cytoscape and associated applications combine data-mining applications with network analysis that facilitate the visualization of data, resulting in an improved understanding of data ( Bindea et al, 2009 ; Cline et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The RNA sequencing techniques revealed that the processes responsible for division are upregulated, whereas the undesirable reactions (immune response, apoptosis) are downregulated in the material with a large number of grain boundaries (UFG Ti). [48] In addition to accelerating the biological response, the biomaterial's surface has to be resistant to bacterial adhesion. Generally, it was observed that nanostructure enhance the proliferation of both osteoblast and bacteria cells, [47,49,50] but different results can be also found in the literature.…”
Section: Grain Refinement To the Nanoscale-an Alternative To Ti6al4vmentioning
confidence: 99%